Responsiveness of the Traumatic Brain Injury Quality of Life Cognition Banks in Recent Brain Injury - Tyner, Callie E.; Kisala, Pamela A.; Boulton, Aaron J.; Sherer, Mark; Chiaravalloti, Nancy D.; Sander, Angelle M.; Bushnik, Tamara; Tulsky, David S. (Frontiers in Human Neuroscience, 2022)
Patient report of functioning is one component of the neurocognitive exam following traumatic brain injury, and standardized patient-reported outcomes measures are useful to track outcomes during rehabilitation. The Traumatic Brain Injury Quality of Life measurement system (TBI-QOL) is a TBI-specific extension of the PROMIS and Neuro-QoL measurement systems that includes 20 item banks across physical, emotional, social, and cognitive domains. Previous research has evaluated the responsiveness of the TBI-QOL measures in community-dwelling individuals and found clinically important change over a 6-month assessment interval in a sample of individuals who were on average five years post injury. In the present study, we report on the responsiveness of the TBI-QOL Cognition–General Concerns and Executive Function item bank scores and the Cognitive Health composite scores in a recently injured sample over a one-year study period. Data from 128 participants with complicated mild, moderate, or severe TBI within the previous 6 months were evaluated. The majority of the sample was male, white, and non-Hispanic. The participants were 18-92 years of age and were first evaluated from 0-5 months post injury. Eighty participants completed the one-year follow-up assessment. Results show acceptable standard response mean values (0.47–0.51) for all measures and minimal detectable change values ranging from 8.2–8.8 T-score points for Cognition–General Concerns and Executive Functioning measures. Anchor rating analysis revealed that changes in scores on the Executive Function item bank and the Cognitive Health composite were meaningfully associated with participant-reported changes in the areas of attention, multitasking, and memory. Evaluation of change score differences by a variety of clinical indicators demonstrated a small but significant difference in the three TBI-QOL change scores by TBI injury severity grouping. These results support the responsiveness of the TBI-QOL cognition measures in newly injured individuals and provides information on the minimal important differences for the TBI-QOL cognition measures, which can be used for score interpretation by clinicians and researchers seeking PRO measures of self-reported cognitive QOL after TBI.